1993
DOI: 10.1159/000227164
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Analysis of Estrogen Receptors in 313 Paraffin Section Cases of Human Thyroid Tissue

Abstract: Three hundred and thirteen cases of human thyroid tissues, comprising 39 nodular goiters from 34 females and 5 males, 130 adenomas from 93 females and 37 males, and 144 carcinomas from 99 females and 45 males were used for the present immunohistochemical assessment of estrogen receptor (ER) expression. Thirty-three cases of follicular carcinoma, 115 cases of papillary carcinoma and 6 cases of anaplastic carcinoma were included in the malignant tumor group. Incidences of ER-positive cases were 23/39 (58.9%) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1
3

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 7 publications
2
19
1
3
Order By: Relevance
“…Papillary carcinomas have an overall higher prevalence, but better prognosis in women of childbearing age, suggesting that sex hormones may influence tumor initiation and growth. 76,77 Similar to previous studies of papillary thyroid carcinoma, [78][79][80][81] expression of ER and PR was increased in the majority of columnar cell carcinomas, but was without discernible gender-or age-specific differences in expression. However, whereas ER expression was detected in the majority of both indolent and aggressive tumors, PR expression was diffusely positive in the majority (three of four) of indolent tumors, but only focally positive in two of five aggressive tumors, implying a possible role for diminished or absent PR expression as a marker for clinicopathologically aggressive columnar cell carcinoma.…”
Section: Discussionsupporting
confidence: 77%
“…Papillary carcinomas have an overall higher prevalence, but better prognosis in women of childbearing age, suggesting that sex hormones may influence tumor initiation and growth. 76,77 Similar to previous studies of papillary thyroid carcinoma, [78][79][80][81] expression of ER and PR was increased in the majority of columnar cell carcinomas, but was without discernible gender-or age-specific differences in expression. However, whereas ER expression was detected in the majority of both indolent and aggressive tumors, PR expression was diffusely positive in the majority (three of four) of indolent tumors, but only focally positive in two of five aggressive tumors, implying a possible role for diminished or absent PR expression as a marker for clinicopathologically aggressive columnar cell carcinoma.…”
Section: Discussionsupporting
confidence: 77%
“…Although in our study we did not noted any significant differences in ER expression between GD and NG, we may not directly compare our results with the results obtained www.fhc.viamedica.pl by Wang et al as the ER expression of ER was not studied in NG lesions [20]. The results of studies analyzing ER expression in NG were inconsistent, as some studies reported even higher ER expression as this noted in our studies, whereas some did not report ERa expression in thyrocytes [21][22][23]. Studies aimed at examining the associations between ER and GD found, that the ESR2 gene was not associated with GD incidence in the Japanese population [24], whereas in the Polish study of Kisiel et al, the authors found a significant association between this gene and GD susceptibility [1].…”
Section: Discussioncontrasting
confidence: 81%
“…Although ER immunostaining was described in less than 10% to over 60% of the samples in the majority of investigations (Haruta et al 1990, Diaz et al 1991, Mizukami et al 1991, Hiasa et al 1993, Lewy-Trenda 1998, Tavangar et al 2007, no ER immunoreactivity was observed in other studies (Jaklic et al 1995, Arain et al 2003. These widely varying results were described for both papillary carcinoma and follicular thyroid carcinoma (FTC) samples.…”
Section: Er Expression In Benign and Malignant Thyroid Tissuesmentioning
confidence: 96%
“…However, widely varying and, in part, contradictory results were reported. Some authors did not find ERs by immunohistochemical staining in normal thyroid tissue and adenomas or goiters (Jaklic et al 1995, Arain et al 2003, while others detected ER staining in approximately 10% to more than 50% of benign thyroid lesions (Diaz et al 1991, Mizukami et al 1991, Hiasa et al 1993, Tavangar et al 2007.…”
Section: Er Expression In Benign and Malignant Thyroid Tissuesmentioning
confidence: 99%
See 1 more Smart Citation